Pembuatan Proyek Pembelajaran IPA "Pertumbuhan dan Perkembangan Hewan dan Tumbuhan" dengan Dokumentasi Seesaw dan Flashcard Quizlet untuk Kelas 4 SD - Sunjayani Allyuwava Kurnywan; Ika Putraviratama (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2026)
Science education in elementary schools requires the active involvement of students through meaningful learning experiences. One of the essential subjects in fourth grade elementary school is the growth and development of animals and plants. However, science education is still often conducted conventionally, so that students' scientific process skills have not developed optimally. This study aims to analyze and describe the application of the Project-Based Learning (PjBL) model in science learning projects on the growth and development of animals and plants with the support of Seesaw and Flashcard Quizlet digital media through a Systematic Literature Review (SLR) approach. The research method used SLR with a descriptive qualitative approach to relevant scientific articles published between 2019 and 2025. The results of the study show that the application of PjBL can increase student learning activity, scientific process skills, and understanding of science concepts. The use of Seesaw was effective as a medium for project documentation and reflection, while Flashcard Quizlet helped reinforce concepts and formative evaluation. Thus, the integration of PjBL, Seesaw, and Quizlet can be an innovative learning alternative that is relevant to the Merdeka Curriculum and the needs of elementary school students.